Delphinidin Inhibits HER2 and Erk1/2 Signaling and Suppresses Growth of HER2-Overexpressing and Triple Negative Breast Cancer Cell Lines - Ozbay, Tuba (Libertas Academica, 2011)
Delphinidin is a polyphenolic compound found in many brightly colored fruits and vegetables. Delphinidin is also the major bioactive component found in many dietary supplements that are currently consumed as complementary cancer medicine including pomegranate extract. The purpose of the current study was to determine the in vitro biological effects of delphinidin on established breast cancer cell lines of varying molecular subtypes in comparison to non-transformed breast epithelial cells. We examined cell proliferation, apoptosis, and growth inhibition in response to delphinidin using a tetrazolium salt-based assay, DNA fragmentation assay, and anchorage-independent growth assay. In comparison to vehicle control, delphinidin inhibited proliferation (P < 0.05), blocked anchorage-independent growth (P < 0.05), and induced apoptosis (P < 0.05) of ER-positive, triple negative, and HER2-overexpressing breast cancer cell lines with limited toxicity to non-transformed breast epithelial cells. MAPK signaling was partially reduced in triple negative cells and ER-negative chemically transformed MCF10A cells after treatment with delphinidin. In addition, delphinidin induced a significant level of apoptosis in HER2-overexpressing cells in association with reduced HER2 and MAPK signaling. Since delphinidin is often consumed as a complementary cancer medicine, the effect of delphinidin on response to specific HER2-targeted breast cancer therapies was examined by proliferation assay. Results of these drug combination studies suggested potential antagonism between delphinidin and HER2-directed treatments. In summary, the data presented here suggest that single agent delphinidin exhibits growth inhibitory activity in breast cancer cells of various molecular subtypes, but raise concerns regarding potential drug antagonism when used in combination with existing targeted therapies in HER2-overexpressing breast cancer.